OP0144 MORTALITY IN GIANT-CELL ARTERITIS PATIENTS: A NATIONWIDE POPULATION-BASED STUDY. (June 2019) - Ben-Shabat, Niv; Amital, Howard; Cohen, Arnon; Comanesther, Doron; Tiosano, Shmuel
Abstract : Background: Giant cell arteritis (GCA), is the most common type of chronic systemic vasculitis over the age of 50. So far, studies regarding mortality in giant-cell arteritis (GCA) patients had yielded conflicting results. Objectives: In this large population-based study we aimed to examine whether GCA is associated with increased mortality in different time periods, and in patients diagnosed ≤ 70 years of age. Methods: We utilized the medical database of the Clalit-Health-Services in a retrospective cohort study. Follow-up was from January 1 st, 2002 and continued until death or end of study follow-up at September 1 st, 2018. Incident GCA patients were compared with age- and sex-matched controls. Estimated median survival-times were calculated using Kaplan-Meyer (KM) method and Risk for all-cause mortality in different follow-up periods was obtained by Cox proportional-hazard model, adjusted for age, gender, socio-demographic variables and traditional risk factors. Results: Our study included 7, 294 GCA patients and 34, 156 age- and sex-matched controls. The mean age at the start of follow-up was 72.11±9.90 years with 69.2% females. The crude mortality rates for the entire follow-up period was 33.4% amongst GCA patients and 30.2% amongst controls. In KM analysis estimated median survival-time was 13.08 years (95% CI, 12.64-13.52 years) in GCA patients compared to 14.35 years (95% CI, 14.09-14.61) in controls ( P -value < 0.001). Cox regression demonstrated increased mortality risk in the first 2 years after diagnosis (HR 1.15; 95% CI 1.04-1.26) and >10 years after diagnosis (HR 1.13; 95% CI 1.02-1.32). Risk was higher in patients diagnosed ≤70 years of age [HR 1.66 (95% CI 1.22-2.13) 0-2 years; HR 1.44 (95% CI 1.16-1.79) > 10 years]. Conclusion: GCA patients have a minor decrease in long-term survival compared to age-and-sex matched controls. The seen difference is due to excess mortality in the first 2 years, and >10 years after diagnosis of GCA, especially in patients diagnosed ≤70 years of age. References: [1] Mohammad AJ, Nilsson J-Å, Jacobsson LTH, Merkel PA, Turesson C. Incidence and mortality rates of biopsy-proven giant cell arteritis in southern Sweden. Ann Rheum Dis [Internet]. 2015 Jun 1 [cited 2018 Aug 10];74(6):993–7. Available from: http://www.ncbi.nlm.nih.gov/pubmed/24442881 [2] Salvarani C, Cantini F, Boiardi L, Hunder GG. Polymyalgia Rheumatica and Giant-Cell Arteritis. N Engl J Med [Internet]. 2002 Jul 25 [cited 2018 Aug 3];347(4):261–71. Available from: http://www.nejm.org/doi/abs/10.1056/NEJMra011913 [3] Hill CL, Black RJ, Nossent JC, Ruediger C, Nguyen L, Ninan J V., et al. Risk of mortality in patients with giant cell arteritis: A systematic review and meta-analysis. Semin Arthritis Rheum [Internet]. 2017 Feb 1 [cited 2018 Aug 4];46(4):513–9. Available from: https://www.sciencedirect.com/science/article/pii/S0049017216301433?via%3Dihub Disclosure of Interests: Niv Ben-Shabat: None declared, Howard Amital Grant/research support from: Pfizer, AbbVie, Janssen, Grant/research support from: Pfizer, AbbVie, Janssen, Consultant for: Pfizer, Merck Sharp & Dohme, Consultant for: Pfizer, Merck Sharp & Dohme, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm, Speakers bureau: Pfizer, Merck Sharp & Dohme, Janssen, Sanofi, Bristol-Myers Squibb, Abbvie, Neopharm, Arnon Cohen Grant/research support from: Prof. Arnon Cohen received research grants from Janssen, Novartis and AbbVie and Sanofi, Consultant for: Prof. Arnon Cohen served as a consultant, advisor for AbbVie; Amgen; Boehringer Ingelheim; Dexcel pharma; Janssen, Lilly; Neopharm; Novartis, Perrigo; Pfizer; Rafa; Sanofi, Speakers bureau: Prof. Arnon Cohen served as speaker for AbbVie; Amgen; Boehringer Ingelheim; Dexcel pharma; Janssen, Lilly; Neopharm; Novartis, Perrigo; Pfizer; Rafa; Sanofi, Doron Comanesther: None declared, Shmuel Tiosano: None declared.